Undeniable : evolution and the science of creation - Nye, Bill (St. Martin's Press, 2014)
"Sparked by a controversial debate in February 2014, Bill Nye has set off on an energetic campaign to spread awareness of evolution and the powerful way it shapes our lives. In Undeniable: Evolution and the Science of Creation, he explains why race does not really exist; evaluates the true promise and peril of genetically modified food; reveals how new species are born, in a dog kennel and in a London subway; takes a stroll through 4.5 billion years of time; and explores the new search for alien life, including aliens right here on Earth. With infectious enthusiasm, Bill Nye shows that evolution is much more than a rebuttal to creationism; it is an essential way to understand how nature works--and to change the world. It might also help you get a date on a Saturday night."